2020
DOI: 10.1007/s10620-020-06618-3
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Steatosis Is Associated with Increased Disease Severity and Liver Injury in Coronavirus Disease-19

Abstract: Background Coronavirus disease-2019 (COVID-19) is a global pandemic. Obesity has been associated with increased disease severity in COVID-19, and obesity is strongly associated with hepatic steatosis (HS). However, how HS alters the natural history of COVID-19 is not well characterized, especially in Western populations. Aims To characterize the impact of HS on disease severity and liver injury in COVID-19. Methods We examined the association between HS and disease severity in a single-center cohort study of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 20 publications
1
59
1
Order By: Relevance
“…Meanwhile, Santos et al reported that dyslipidemia as an independent predictor of mortality 19 . Obesity and chronic liver disease, including fatty liver disease, may affect the association between dyslipidemia and poor outcome; because both obesity and fatty liver disease are associated with poor prognosis 24 , 25 , 26 . However, meta-regression analysis was not possible because only three studies were reporting chronic liver disease, and one study reporting obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Santos et al reported that dyslipidemia as an independent predictor of mortality 19 . Obesity and chronic liver disease, including fatty liver disease, may affect the association between dyslipidemia and poor outcome; because both obesity and fatty liver disease are associated with poor prognosis 24 , 25 , 26 . However, meta-regression analysis was not possible because only three studies were reporting chronic liver disease, and one study reporting obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Another cohort study of 342 patients with COVID-19 revealed a relationship between hepatic steatosis and both transaminitis and increased disease severity. However, steatosis did not predispose to the development of clinically relevant liver insufficiency during the course of infection[ 75 ].…”
Section: Metabolic Syndrome and Inflammation As Factors Predisposing mentioning
confidence: 99%
“…In fact, elder ( Li et al, 2020a ; Yu et al, 2020 ) and male ( Feng et al, 2020 ; Kaushik et al, 2020 ) COVID-19 patients seem most prone to develop liver damage. Patients with pre-existing liver pathologies, in particular non-alcoholic steatohepatitis or metabolic-associated fatty liver disease, show higher liver injury in the course of the disease ( Chen et al, 2021 ; Gao et al, 2021 ; Pan et al, 2021 ), yet others were not able to establish a link between chronic liver disease and mortality/severity of COVID-19 ( Lippi et al, 2021 ; Palomar-Lever et al, 2020 ).…”
Section: Covid-19 and The Livermentioning
confidence: 99%